Analysis of Marketing Channels and Factors Affecting the Selling Price of Cassava in Martapura District, Ogan Komering Regency, East Ulu - nanda ali mustofa; Endang Lastinawati; ema pusvita (Jurnal Ilmiah Mahasiswa AGROINFO GALUH, 2026)
This study aims to analyze marketing channels and identify factors that affect the selling price of cassava in Martapura District, Ogan Komering Ulu Timur Regency. The method used is a survey method with a quantitative approach and descriptive analysis techniques as well as multiple linear regression. Primary data were obtained from 46 cassava farmer respondents who were selected purposively. The results of the study show that there are two main marketing channels, namely: (1) farmers → collectors → factories → consumers, and (2) farmers → collectors → individual businesses → consumers. The first channel has a higher efficiency (11.62%) and a farmers share of 14.06%, compared to the second channel (efficiency of 12.31%, farmers share of 12.63%). The results of the regression analysis showed that the variables of cassava quality and marketing institutions had a significant effect on the selling price, while demand was significant at the level of 10%. Meanwhile, weather variables and production costs did not have a significant effect. These findings show that institutional strengthening and improving product quality are strategic keys in increasing the selling value of cassava at the farmer level. Keywords: Efficiency, Selling Price, Farmer, Cassava Marketing Channel